2015
DOI: 10.1016/j.meegid.2014.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of genome evolution of Streptococcus

Abstract: The genus Streptococcus contains 104 recognized species, many of which are associated with human or animal hosts. A globally prevalent human pathogen in this group is Streptococcus pneumoniae (the pneumococcus). While being a common resident of the upper respiratory tract, it is also a major cause of otitis media, pneumonia, bacteremia and meningitis, accounting for a high burden of morbidity and mortality worldwide. Recent findings demonstrate the importance of recombination and selection in driving the popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 95 publications
0
62
0
Order By: Relevance
“…This was 75 additional pan-genomic families compared to the study of Zheng et al 41 , which is surprisingly few, since this study included three times the number of genomes. Previous studies have shown that Streptococcus has an open pan-genome and frequent recombination that leads to gene gain and loss within Streptococcus 8,41,45 . Therefore, the size of the pan-genome is expected to increase as the number of genomes increases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was 75 additional pan-genomic families compared to the study of Zheng et al 41 , which is surprisingly few, since this study included three times the number of genomes. Previous studies have shown that Streptococcus has an open pan-genome and frequent recombination that leads to gene gain and loss within Streptococcus 8,41,45 . Therefore, the size of the pan-genome is expected to increase as the number of genomes increases.…”
Section: Discussionmentioning
confidence: 99%
“…Natural genetic transformation, by uptake as well as release of DNA, has been described in several species belonging to the Mitis Group streptococci 1,7 . This genetic competence is an important mechanism for acquiring genes involved in biofilm formation, adherence and resistance to host immune systems [7][8][9] .…”
mentioning
confidence: 99%
“…28,29 Next we observed rapid reductions in certain additional PCV13 serotypes ∼3 years after introduction of PCV13, although, notably, serotypes 19A and 3 continued to be present at low rates in 2014. Possible reasons for the persistence of 19A and 3 include genetic diversity leading to less effective immune responses 22,30,31 or selection pressure from recent antibiotic use. 32 -34 Of note, first-line penicillins continue to be the most frequently prescribed antibiotic across all age groups among young children in Massachusetts, which may result in the continued success of 19A associated with penicillin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Highly conserved surface proteins of the pneumococcus are also attractive vaccine candidates, although the diverse pangenome of pneumococcus (43), especially that of the nontypeable strains (47), can result in a diverse repertoire of surface proteins among strains (43). Therefore, multivalent vaccines may have the greatest potential to provide the broadest protection against multiple serotypes and nonencapsulated pneumococci.…”
Section: Discussionmentioning
confidence: 99%